Approaches to Managing Speed in New Zealand’s Capital - Sandra Mandic; Joe Hewitt; Nadine Dodge; Neha Sharma (Journal of Road Safety)
Higher speeds increase the risk of crashes occurring and the severity of resulting injuries. The purpose of speed management is to ensure that speeds are safe for all road users thereby reducing the number of crashes and avoiding injuries and deaths when crashes happen. In response to a rising trend in deaths from road crashes in recent years, the New Zealand Government introduced the Road to Zero road safety strategy in 2018 and updated the Land Transport Rule: Setting of Speed Limits in 2022. In Wellington city (New Zealand’s capital), unsafe speed limits and high numbers of road crashes with injuries make city streets unsafe, have high social costs, present a barrier to active transport, and limit mode choice for residents and visitors. This study assessed nine speed management options using cost benefit analysis. Citywide permanent speed reduction was most effective for reducing road crash-related injuries, but benefits were outweighed by travel time disbenefits. The option with 30 km/h speed limit for local streets and 40 km/h for arterial streets had the highest crash reduction benefits of over NZD $250 million discounted over 40 years, followed by the option of 30 km/h default citywide, albeit with the high construction costs and relatively high vehicle travel time disbenefits. Incremental cost benefit calculations indicated that the most efficient options were permanent speed reductions near schools. Implementing variable speed limits around schools provided the lowest benefits and very low value for money compared to citywide speed management approaches or permanently reduced speed around schools.